2019
DOI: 10.17235/reed.2019.6155/2019
|View full text |Cite
|
Sign up to set email alerts
|

The status of proton pump inhibitor use: a prescription survey of 45 hospitals in China

Abstract: Background: proton pump inhibitors (PPI) have been widely used in the clinic but inappropriate prescribing has also increased dramatically. Objective: to describe the prescribing patterns and assess the appropriateness of the p rescribed PPI use in 45 hospitals in China. Materials and methods: PPI prescriptions for non-hospitalized patients were collected from hospitals in Beijing, Chengdu, Guangzhou and Hangzhou of China over a 40-day period in 2016. These data were analyzed using the prescription number, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 26 publications
3
35
1
2
Order By: Relevance
“…In the Icelandic study, 95% of patients started high dose PPI (they defined this “high dose” category as standard dose or high dose), and 21% remained on that treatment after 1 year ( Halfdanarson et al., 2018 ). Similar overdosing of PPIs has been reported from China ( Ying et al., 2019 ).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the Icelandic study, 95% of patients started high dose PPI (they defined this “high dose” category as standard dose or high dose), and 21% remained on that treatment after 1 year ( Halfdanarson et al., 2018 ). Similar overdosing of PPIs has been reported from China ( Ying et al., 2019 ).…”
Section: Discussionsupporting
confidence: 85%
“…Other studies from inpatients reported a high discordance from evidence-based indications of PPI use (Pillans et al, 2000;Chia et al, 2014;Meli et al, 2015;Lodato et al, 2016;Pujal Herranz, 2016;van den Bemt et al, 2016;Ying et al, 2019). In the expert review of Savarino et al PPIs are considered as "harmless, cheap remedy for any digestive problems by doctors" (Savarino et al, 2018a).…”
Section: Initiation/de-prescribing Ppismentioning
confidence: 99%
See 2 more Smart Citations
“… 7 In recent years, the irrational use of PPIs has become common in China, mainly involving unapproved indications and excessive dosages. 8 , 9 In addition, the negative effects of PPI use are generally underestimated owing to marketing and reporting bias in published trials. Widespread and inappropriate use of PPIs is likely to translate into serious long-term adverse effects such as increased gastrointestinal tract infections (e.g., Clostridium difficile -associated diarrhea), reduced intestinal absorption of vitamins and minerals, pneumonia, increased fracture risks, 10 14 kidney damage 15 , 16 and liver adverse effects.…”
Section: Introductionmentioning
confidence: 99%